Differential Regulation of Escherichia coli fim Genes following Binding to Mannose Receptors. (22nd May 2018) - Schwan, William R.; Beck, Michael T.; Hung, Chia S.; Hultgren, Scott J.
Abstract : Regulation of the uropathogenic Escherichia coli (UPEC) fimB and fimE genes was examined following type 1 pili binding to mannose-coated Sepharose beads. Within 25 min after mannose attachment, fimE expression dropped eightfold, whereas fimB transcription increased about two- to fourfold. Because both fim genes encode site-specific recombinases that affect the position of the fimS element containing the fimA promoter, the positioning of fimS was also examined. The fimS element changed to slightly more Phase-OFF in bacteria mixed with plain beads, whereas UPEC cells interacting with mannose-coated beads had significantly less Phase-OFF orientation of fimS under pH 7 conditions. On the other hand, Phase-OFF oriented fimS increased fourfold when UPEC cells were mixed with plain beads in a pH 5.5 environment. Positioning of fimS was also affected by fimH mutations, demonstrating that the FimH ligand binding to its receptor facilitates the changes. Moreover, enzyme immunoassays showed that UPEC cells had greater type 1 pili expression when mixed with mannose-coated beads versus plain beads. These results indicate that, after type 1 pilus binding to tethered mannose receptors, the physiology of the E. coli cells changes to maintain the expression of type 1 pili even when awash in an acidic environment.